Speciﬁc course of COVID-19 associated pneumonia in the tuberculosis patient after pleuropneumonectomy - E. M. Zhukova; Zh. A. Laushkina; D. A. Skvortsov; N. V. Stavitskaya (Туберкулез и болезни лёгких, 2022)
The article describes a clinical case of viral pneumonia associated with COVID-19 of the only lung, it developed in the patient 30 days after pleuropneumonectomy which was done to manage ﬁbrous cavernous pulmonary tuberculosis. The favorable course of COVID-19 was due to its timely detection and initiation of treatment, and possibly, it was due to using anti-tuberculosis chemotherapy containing antibacterial drugs that prevented nosocomial infections.